2015
DOI: 10.1158/0008-5472.can-14-3265
|View full text |Cite|
|
Sign up to set email alerts
|

Diverse Targets of β-Catenin during the Epithelial–Mesenchymal Transition Define Cancer Stem Cells and Predict Disease Relapse

Abstract: Wnt signaling contributes to the reprogramming and maintenance of cancer stem cell (CSC) states that are activated by epithelial-mesenchymal transition (EMT). However, the mechanistic relationship between EMT and the Wnt pathway in CSC is not entirely clear. Chromatin immunoprecipitation with highthroughput sequencing (ChIP-seq) indicated that EMT induces a switch from the b-catenin/E-cadherin/Sox15 complex to the b-catenin/Twist1/TCF4 complex, the latter of which then binds to CSC-related gene promoters. Tand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 47 publications
2
70
0
Order By: Relevance
“…However, the mechanistic relationship between EMT and the Wnt/β-catenin pathway is not entirely clear. Chromatin immunoprecipitation with high-throughput sequencing indicated that EMT induces a switch from the β-catenin/E-cadherin/Sox15 complex to the β-catenin/Twist1/TCF4 complex, which then binds to cancer stem cell-related gene promoters [32]. In our study, we found that C/EBPα suppressed β-catenin/TCF/LEF complex transcriptional activity and downregulated levels of β-catenin and its downstream targets.…”
Section: Discussionmentioning
confidence: 49%
“…However, the mechanistic relationship between EMT and the Wnt/β-catenin pathway is not entirely clear. Chromatin immunoprecipitation with high-throughput sequencing indicated that EMT induces a switch from the β-catenin/E-cadherin/Sox15 complex to the β-catenin/Twist1/TCF4 complex, which then binds to cancer stem cell-related gene promoters [32]. In our study, we found that C/EBPα suppressed β-catenin/TCF/LEF complex transcriptional activity and downregulated levels of β-catenin and its downstream targets.…”
Section: Discussionmentioning
confidence: 49%
“…LGR5 potentiates Wnt/β-catenin pathway in BCSCs and is required for the maintenance of spheroid-derived CD44+/CD24− BCSCs [245]. During EMT, β-catenin binds to Twist1 to increases the transcriptional activity of β-catenin/TCF4 complex by binding to the promoter DNA of ABCG2, a cancer stemness marker [246]. …”
Section: Her2 Promotes Stemness Signaling Pathwaysmentioning
confidence: 99%
“…β-catenin, one key protein in Wnt signaling, separates from the degradation complex and then accumulates in the cytoplasm, translocates into nucleus subsequently to sensitize the Wnt pathway during Interaction between Wnt/β-catenin pathway and microRNAs regulates epithelial-mesenchymal transition in gastric cancer (Review) carcinoma progression. In the presence of downregulation of E-cadherin and Wnt signals activation, both cytoplasmic and nuclear levels of β-catenin increase where it interacts with cell growth and EMT (7,8). MicroRNAs are small noncoding molecules with 19-25 nucleotides that bind to 3'UTR of target mRNAs with complementary base pairing to inhibit their translation or speed up decomposition.…”
Section: Introductionmentioning
confidence: 99%